ANIMAL IDIOMS IN ENGLISH - Masrul Huda (UIN Alauddin Makassar, 2019)
This study aimed to describe the idiom usage in English, both its functions in sentences and the meaning. It also tries to describe the link between idioms and culture. The data are taken from Mc Graw Hill's Dictionary of American Idioms and Phrasal Verbs by Richard A. Spears, Ph.D and A Book of English Idioms by V.H. Collins. The finding shows that form of idioms are phrase, clause, and sentence. The phrase patterns are Animal Element (AE) + Noun, Adjective + Animal Element (AE), Verb + Animal Element (AE), Animal Element (AE) + Preposition, and Animal Element (AE) + Verb. The idioms functions are as Verb, Adjective, and Noun. The study also finds a relation between idiom and culture.ABSTRAKPenelitian ini bertujuan untuk menggambarkan penggunaan idiom di dalam bahasa Inggris, termasuk fungsi dalam kalimat dan artinya. Penelitian ini juga berusaha untuk menggambarkan hubungan antara idiom dan budaya setempat. Data diperoleh dari Mc Graw Hill's Dictionary of American Idioms and Phrasal Verbs karangan Richard A. Spears, Ph.D and A Book of English Idioms yang ditulis oleh V.H. Collins. Penelitian ini menunjukkan bahwa idiom di dalam bahasa Inggris bisa berbentuk frase, klausa, dan kalimat. Pola frase Unsur Hewan + Kata Benda, Kata Sifat + unsur Hewan, Kata Kerja + Unsur Hewan, Unsur Hewan + Preposisi, dan Unsur Hewan + Kata Kerja. Idiom tersebut dapat berfungsi sebagai Kata Kerja, Kata Sifat, dan Kata Benda. Penelitian ini juga menunjukkan hubungan antara idiom dan budaya setempat. Kebudayann memberi pengaruh penggunaan idiom.Kata Kunci: Idiom, Hewan, Arti, Budaya